Education for the “Freebies” Generation: Teenage Mothers in the Classrooms (American Journal of Youth and Women Empowerment, 2025)
With barely half a decade remaining to achieve the UN Sustainable Development Goals (SDGs) targets outlined in the 2030 Agenda, and as part of the promise to equitable, inclusive, and quality education for all (SDG 4.5), the effective and efficient practices of girl-child education and empowerment are recognized. In qualitative case study fieldwork in the Ayensuano District in the Eastern Region of Ghana, data from 83 assistant headteachers during a workshop/conference on Child Labour Issues and Safe School Environment was gathered through unstructured discussion or interview. This was to better understand teachers’ and parents’ talk on basic education for teenage mothers in the light of Ghana’s Inclusive Education Policy. The discussion discloses interesting perspectives from teachers and parents about adolescent mothers in the classrooms such as the uncritical behaviour of a “freebies” generation, the needless pampering of teenage mothers or expectant mothers which will be a form of insult to unmarried/childless/infertile teachers., the poorly resourced nature of our schools to cater for them, an addition to the already large workload of teachers, and a negative form of influence on ‘good’ or ‘morally upright’ students. Could these perspectives fit the “progressive” description of Ghana’s Basic Education, the UN Sustainable Development Goal (SDG) 4.5, the Era of Leaving No Child Behind, and the hope of building the World We Want?